“Tem outro jeito de fazer, moço!”: apropriação de práticas de numeramento escolares por estudantes de Licenciatura em Matemática da Uneb – Caetité - Gildelson Felicio de Jesus (2021)
In this investigation, we analyze ways of appropriating school Analytical Geometry numeracy practices enacted by students in the Mathematics Teaching Degree at Uneb, Campus VI, city of Caetité-Bahia-Brazil, grounded on their student experiences on K-12 and/or higher education. As part of the research program developed by the UFMG Study Group on Numeracy - GEN, we consider numeracy practices as discursive practices of a certain cultural group. These are configured in the ways of producing, circulating, transmitting, using, and evaluating positions demanded in interlocutive games that involve ideas, representations and procedures we recognize as mathematical, marked by intentions and values that shape the culture of this group. The research has a qualitative approach. The empirical data was collected in two phases: (1) application of a questionnaire to profile the undergraduates of the Mathematics Teaching Degree at Uneb-Caetité and to obtain a wide range of information on their relationship with school mathematics, mainly Analytical Geometry; and (2) focus groups with these students discussing of and about Analytical Geometry, in which the undergraduates assumed discursive positions that conform and express their efforts of meaning, establishing the appropriation of numeracy practices. In our analysis, we focused on events identified in one session of a focus group, in which undergraduates solved Analytical Geometry questions created by students from another focus group. This analysis is based on the characterization of the elements that make up the mathematical discourse (vocabulary, visual mediators, routines and narratives) developed by Anna Sfard. We were not interested in evaluating mistakes and successes when reflecting on decisions and positions on the routines, visual mediators and vocabulary, chosen by students to produce their narratives to solve the problems in the list of exercises. By weaving an understanding of ways of appropriating numeracy practices as processes of a discursive nature, we wanted to contribute to the recognition, acceptance, elaboration, and development of answers to the demands and the contributions of these subjects, whose teacher training we have the opportunity and responsibility to participate.